2012
DOI: 10.7439/ijbr.v3i2.296
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Encephalitis in Children in Bellary Karnataka: Clinical Profile and Sequelae

Abstract: Objectives:To study the clinical profile and outcome of Japanese Encephalitis(JE) Methods: Prospective study was done in Vijayanagara Institute Medical Sciences hospital, Bellary, Karnataka. 233 patients below 12 years of age presented with acute encephalitic picture during the epidemic period formed the subjects and were worked up according to a predesigned protocol. CSF and serum samples were tested for JE specific IgM antibodies. Patients were followed up for 4 months to over one year. Results: The predomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
8
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 9 publications
4
8
1
Order By: Relevance
“…In children similar manifestation was also noted in earlier studies [25, 26]. Signs of meningeal irritation were frequently observed in more than half of the study patients as recorded in other studies [1, 27].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In children similar manifestation was also noted in earlier studies [25, 26]. Signs of meningeal irritation were frequently observed in more than half of the study patients as recorded in other studies [1, 27].…”
Section: Discussionsupporting
confidence: 88%
“…However, in a study by Avabratha et al observed elevated cell count in 45.06% and protein in 74.67% study patients [26]. …”
Section: Discussionmentioning
confidence: 99%
“…These findings are comparable to other studies. 13,19,20 However, the study by Roy et al found a higher JE mortality of 54.55% in children aged 1 month to 12 years. 9 71% of JE patients were found to have been discharged from hospital in our study, but the proportion of these patients having intact neurological survival and the presence of sequelae at the time of discharge could not be studied.…”
Section: Discussionmentioning
confidence: 98%
“…The birds are the main reservoir hosts along with pigs as major amplifying hosts, while human beings and horses are the incidental (dead end) hosts associated with this disease [ 6 ]. In southern part of India, co-infection of cysticercosis and JE in children has been reported, in which pigs were the intermediate as well as amplifying hosts for these diseases [ 50 ].…”
Section: Jementioning
confidence: 99%